Self-excision of the antibiotic resistance gene npII using a heat inducible Cre-loxP system from transgenic potato - Cuéllar, Wilmer Jose; Gaudin, A.; Solorzano, D.; Casas, A.; Nopo, L.; Chudalayandi, P.; Medrano, G.; Kreuze, Jan F.; Ghislain, M. (Springer, 2006)
Resistance to antibiotics mediated by selectable marker genes remains a powerful selection tool for transgenic event production. However, regulatory agencies and consumer concerns favor these to be eliminated from food crops. Several excision systems exist but none have been optimized or shown to be functional for clonally propagated crops. The excision of the nptII gene conferring resistance to kanamycin has been achieved here using a gene construct based on a heat-inducible cre gene producing a recombinase that eliminates cre and nptII genes flanked by two loxP sites. First-generation regenerants with the Cre- loxP system were obtained by selection on kanamycin media. Following a heat treatment, second generation regenerants were screened for excision by PCR using nptII, cre, and T-DNA borders primers. Excision efficiency appeared to be at 4.7% depending on the heat treatment. The footprint of the excision was shown by sequencing between T-DNA borders to correspond to a perfect recombination event. Selectable marker-free sprouts were also obtained from tubers of transgenic events when submitted to similar heat treatment at 4% frequency. Spontaneous excision was not observed out of 196 regenerants from untreated transgenic explants. Biosafety concerns are minimized because the expression of cre gene driven by the hsp70 promoter of Drosophila melanogaster was remarkably low even under heat activation and no functional loxP site were found in published Solanum sequence database. A new plant transformation vector pCIP54/55 was developed including a multiple cloning site and the self-excision system which should be a useful tool not only for marker genes in potato but for any gene or sequence removal in any plant.